Importance of the flexner report in the development of Ukrainian medical education - Куліченко, Алла Костянтинівна; Kulichenko, Alla (Nowy Sacz: National-Louis University, 2017)
Today Ukrainian medical education is on the way to modernization and reformation. This is due to the goals: to develop well-trained, high-toned, healthy citizens of Ukraine, and to analyze and synthesize significant international educational practice in order to choose the best cpncepts, systems, information and communication technologies for their further practical usage. Thus, there is an urgent need in focusing on American medical education and highlighting important aspects of learning experience. In this paper, we briefly dwell upon the Flexner Report (1910).